ابن عربي التصوف - بدوي، علي محمد (جامعة تشرين, 2017)
التصوف: هو علم يقصد به تزكية النفوس وصفاء القلوب وإصلاح الأخلاق والوصول إلى مرتبة الإحسان. فهذا العلم قد حاربته بعض الجهات لتدمير روح الإسلام والتوجه إلى الإشكاليات التي سعت إلى دمار الإسلام الوسطي المتسامح، وليس فقط كفكر بل حاربت رجالاته الذين كانوا لهم السابقة بنشر الفلسفة الدينية والتسامح الاجتماعي، ولا سيما ابن عربي ذلك الرجل الفيلسوف الذي ضاقت عليه الدنيا بما رحبت من أفكاره ونظرياته ومؤلفاته ورحلاته التي تحتاج لمجلدات للحديث عنها، وبالرغم من عظمة هذا العالم فقد ظهرت ثلة من المعارضين له الذين اتهموه بالكفر البواح وهو من ذلك براءة، وذلك لأنهم حملوا أفكاره ونصوصه على ظاهرها دون الوقوف على جوهر مراده وقصده.
Sufism is a science intended to purification the souls and clean heart and reforming morality and access to the rank of charity. This science has been fought by some groups to destroy the spirit of Islam and its orientation to the problems that have sought to destroy the moderate tolerant Islam, and not just as ideology but fought its statesmen who have previous publication of religious philosophy and social tolerance, especially Aben Arabe, the philosopher, who the world could not be enough to his ideas, theories, writings and his trips that require volumes to talk about. Despite the greatness of this scientist a group of opponents, who accused him of blasphemy outright from which so innocent, emerged. So they took up his ideas and texts on the face of it without standing on the essence of what he meant or wanted.
Keywords: الفكر الصوفي -- الصراعات الفكرية -- المعتقدات الدينية -- المذاهب الإسلامية